Bending properties in the 4‐halobenzonitrile crystals and C–halogen…N[triple‐bond]C halogen bonds. Issue 12 (9th November 2022) - Veluthaparambath, Ragima V. P.; Krishna G, Vibha; Pancharatna, Pattath D.; Saha, Binoy K.
Abstract : We have analyzed why single crystals of 4‐chlorobenzonitrile and 4‐bromobenzonitrile are compliant but 4‐iodobenzonitrile is brittle. Geometry‐corrected statistical analysis and DFT calculations both suggest that the C—I…N[triple‐bond]C halogen bond is stronger, as well as highly directional, compared to its bromo and chloro counterparts, which make the iodo crystal brittle. Abstract : The single crystal of 4‐iodobenzonitrile (C7 H4 IN) is brittle, whereas those of 4‐bromobenzonitrile (C7 H4 BrN) and one of the two forms of 4‐chlorobenzonitrile (C7 H4 ClN) are compliant in nature. The chloro crystal exhibits elastic bending, but in spite of having stronger halogen bonds, the bromo crystal exhibits plastic bending. Crystal structures have been analyzed to understand the different bending properties of these three crystals. In all three cases, the molecules form C— X …N[triple‐bond]C ( X  = halogen) halogen‐bonded chains in their respective crystal structures. Statistical analyses and DFT calculations on the C— X …N[triple‐bond]C halogen bonds reveal that the optimum geometry of all three halogen bonds is linear and the C—I…N[triple‐bond]C bond is strongest among the three. However, when the geometry deviates from linearity, the energy loss is very high in the case of the C—I…N[triple‐bond]C bond compared to the other two systems. This explains why 4‐iodobenzonitrile is brittle, whereas the other two are flexible. The interactions in 4‐bromobenzonitrile are more isotropic than those in 4‐chlorobenzonitrile. The iodo and chloro compounds crystallize in centrosymmetric space groups, whereas the crystal of the bromo compound lacks inversion symmetry. In spite of this difference in their space groups, the chloro and bromo crystals have very similar crystal packing. In the case of the bromo crystal, the halogen‐bonded chains are parallel to the bending axis (long axis) of the crystal. However, these chains are significantly tilted in the case of the chloro crystal. The isotropic/anisotropic interactions, presence/absence of an inversion centre and the different alignment of the halogen‐bonded chains with respect to the bending axis could explain the different bending properties of the chloro and bromo crystals.